Using questionnaire design to fight non-response bias in web surveys - Vicente, P.; Reis, E. (Social Science Computer Review, 2010)
The technical potential of the Internet offers survey researchers a wide range of possibilities for web surveys in terms of questionnaire design; however, the abuse of technical facilities can detract respondents from cooperating rather than motivating them. Within the web survey methodology literature, many contributions can be found on how to write a "good" questionnaire. The outcomes are however scattered and researchers and practitioners may find it difficult to obtain an overall picture. The article reviews the latest empirical research on how questionnaire characteristics affect response rates. The article is divided into three main sections: an introduction where the various forms of nonresponse in web surveys are described; a second section presenting questionnaire features affecting nonresponse-general structure, length, disclosure of survey progress, visual presentation, interactivity, and question/response format and a final section that summarizes the options in terms of questionnaire design and its implications for nonresponse rate.